Characterization and evaluation of a novel immunochromatographic assay for pharyngealMycoplasmapneumoniaeribosomal protein L7/L12 antigens. Issue 10 (18th October 2016) - Sano, Go; Itagaki, Tsutomu; Ishiwada, Naruhiko; Matsubara, Keita; Iwata, Satoshi; Nakamori, Yoshitaka; Matsuyama, Kenji; Watanabe, Katsuya; Ishii, Yoshikazu; Homma, Sakae; Tateda, Kazuhiro
Abstract : N/A: Point‐of‐care testing for Mycoplasma pneumoniae infection may be ideal and useful because significant numbers of the cases will be seen as outpatients. Recently, a new immunochromatographic method (ICM) targeting M. pneumoniae ribosomal protein L7/L12 (RP‐L7/L12) in pharyngeal swabs became available in Japan, although clinical data and basic information regarding efficacy and characterization of this ICM are limited. The present study examined the fate of M. pneumoniae RP‐L7/L12 during in vitro growth and the correlation between M. pneumoniae concentration in clinical specimens and the sensitivity of the ICM test. The usefulness of the ICM was investigated in patients suspected of having M. pneumoniae pneumonia and upper respiratory tract infection (137 children and 39 adults). The limit of detection for the ICM test was 1.1×10 4 c.f.u. ml −1 of M. pneumoniae . Bacterial production of RP‐L7/L12 correlated positively with the viable M. pneumoniae concentration in vitro ; antigen was then degraded in culture broth, with an in vitro half‐life of approximately 2 days. Five other Mycoplasma spp. and 14 representative respiratory pathogens were ICM assay negative at bacterial concentrations of 10 6 c.f.u. ml −1 . The clinical sensitivity and specificity of the ICM assay were 57.1 % (20/35) and 92.2 % (130/141), respectively, in comparison with bacterial culture. Clinical specimens containing ≥10 6 c.f.u. ml −1 of M. pneumoniae burden were ICM positive in 13 of 18 cases (72.2 %). The ICM is a poorly sensitive but reasonably specific means for detecting M. pneumoniae infections.